Parametric analysis of self-excited aeroelastic instability of an isolated single-axis two-dimensional flat solar tracker - Juan A. Cárdenas-Rondón; Carlos Carbajosa; Sergio Marín-Coca; Alejandro Martínez-Cava (Results in Engineering)
The escalating global energy demand is driving a transition towards sustainable energy sources, particularly solar power, which is experiencing significant growth. Single-axis, horizontally mounted photovoltaic (PV) solar trackers are emerging as one of the most cost-effective methods for solar energy generation. However, the reduction in structural stiffness has led to an increase in aeroelastic issues, some of which have resulted in catastrophic failures around the world, posing significant challenges. Recent aerodynamic studies have attributed these instabilities to stall flutter. The absence of a validated theory hampers early estimation of these aeroelastic phenomena. The primary aim in this work is to develop a semi-empirical framework to predict aeroelastic instabilities in isolated two-dimensional solar trackers, focusing on dynamic self-excited responses. This effort aims to improve the reliability and efficiency of solar tracker designs, optimizing energy utilization in the context of the evolving renewable energy landscape. The semi-empirical formulation developed here reveals the influence of geometric and mechanical characteristics on the critical wind speed at which aeroelastic instabilities set in. The effects of reduced inertia (m⁎) and mechanical damping coefficient (ξmech) of the structure on the critical wind speed at which aeroelastic instabilities arise are analyzed here. It is shown that increasing either inertia or damping has a minor impact on the critical speed when the initial values of these parameters are large, while the changes are significant when these initial values are small.